Eletrofiação de nanofibras de KBiFe2O5 com potencial aplicação em células solares - Melo, Guilherme Henrique França (Universidade Federal de São Carlos, 2020)
Today, ferroelectric semiconductors with perovskite type structure are widely studied due to the possibility of obtaining voltages higher than their band gap and to their contribution to the charge carriers’ separation due to the intrinsic polarization of these materials. Ferroelectric oxides usually have high Eg (2.70 - 4.00 eV), which allows only harnessing 8-20 % of the solar spectrum. However, the development of new ferroelectric semiconductors like KBiFe2O5 (KBFO) (Eg = 1.60 eV), has encouraged the application of these materials in solar cells. Routes of chemical synthesis, with reduced times and temperatures are essential, however, for the future application of these oxides in solar cells. KBFO was discovered in 2013 as an alternative to BiFeO3 (BFO) (Eg = 2.70 eV); however, until now, this material has only been synthesized at temperatures equal or higher than 650 °C, which difficult its application in photovoltaic devices. Besides, due to the high resistivity of the KBFO, recombination of the charge carriers is facilitated, thus decreasing its potential; this problem can be diminished, however, by reducing the thickness of the sample. In this work, the KBFO phase was obtained through two routes with a polymer as an additive (PVP), sol-gel synthesis and electrospinning, using five different heat treatments. The formation of the phase was confirmed by X-Ray Diffraction, the presence of the phase was confirmed for synthesis temperatures above 550 ° C and the non-formation for the temperature of 500 ° C; the morphology of the samples was analyzed using Scanning Electron Microscopy, proving the nanometric dimension in the samples obtained through the electrospinning process; the band gap value was obtained through absorption spectroscopy in the Ultraviolet-Visible region (UV-Vis), presenting a band gap close to 1.75 eV. The work presented two unprecedented results: obtaining the KBFO phase at temperatures below 650 ° C (without the use of high pressures) and obtaining nanofibers from this phase.
Electrospinning of KBiFe2O5 nanofibers with potential application in solar cell devices
Keywords: KBiFe2O5; Eletrofiação; Perovskita; Energia solar; Electrospinning; Perovskite; Solar energy; ENGENHARIAS::ENGENHARIA DE MATERIAIS E METALURGICA::MATERIAIS NAO METALICOS